PPM UKM MAS BRO SABLON KELURAHAN SUMBEREJO KECAMATAN PAKAL KOTA SURABAYA - suryo atmojo; Ruli Utami; Suzana Dewi; Nurwahyudi Widhiyanta; Nur Ali Sholikin (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
Mas bro sablon is a micro screen printing business owned by Angga's brother which is located on Jl. Citra Raya Lakarsantri No.9A, Lakarsantri, Kec. Lakarsantri, City of SBY, East Java 60211. This screen printing micro business has different characteristics when viewed from the type of screen printing business offered. This micro-screen printing business only focuses on t-shirt printing, while the second micro-screen printing business is more varied, besides plastic screen printing, it also accepts orders for books and notes. Business partners only work on their products based on orders or with a job order cost system. What is meant by Job Order Cost System is a method of collecting production costs applied to companies that produce products on an order basis. This method is most appropriate to be applied when the types of materials and methods of implementation are different. Each product is usually made according to the specifications of the buyer's order, while the price offered is closely related to the estimated cost. Based on interviews with business owners, bro screen printing, the obstacles while pursuing the screen printing business are promotional media that are still lacking updates, limited image design capabilities, no tools or systems for financial recording, production SOPs do not yet exist, customer orders sometimes change, process less than optimal drying (still using a hot gun) and the number of tables which are only 8 are deemed insufficient to meet the production capacity. From the existing problems, the solutions offered are conducting design training, training on order and financial recording tools, making production SOPs, as well as adding tables and training on the use of curing tools to maximize the drying process of screen printing results.